Changes of fatty acid profiles in mushroom corals (Fungia fungites) after short-term laboratory exposure to anti-fouling herbicide diuron - Hassan Rashid Ali,; Che Din Mohd Safuan,; Aminudin Muhammad Afiq-Firdaus,; Mohammad Ali Sheikh,; Marinah Mohd Ariffin,; Wan Izatul Asma Wan Talaat,; Zainudin Bachok, (Penerbit Universiti Kebangsaan Malaysia, 2024)
There is a great concern about the recent use of new anti-fouling chemicals for boats and ships to the coral reef health. Diuron is one of the new anti-fouling paints after the ban of organotin as an anti-fouling system (AFS) compound, but yet to be proven safe for the marine environment. Presently, we demonstrated the effects of Diuron on the fatty acid composition of hard coral species (Fungia fungites) in the laboratory. The corals were exposed to different doses of Diuron under short-term exposure (96 hr) and the fatty acid (FA) compositions of the coral tissues were determined using the gas chromatography technique. The fatty acid composition between fresh and control samples of F. fungites was significantly similar where both samples were dominated by Saturated FA (SAFA), followed by Polyunsaturated FA (PUFA) and Monounsaturated FA (MUFA). In contrast, the trends for exposed samples (20, 100 & 500 μg/L) of F. fungites showed a significant decrease (P<0.05) of SAFA, MUFA, and PUFA with species suffering more as the dose of diuron increased. As the level of dose increased, SAFA such as 16:0 was largely affected while unsaturated FA from ω3 and ω6 series showed a slight decrease in their composition. The decrease in fatty acid composition after Diuron exposure indicates that the anti-fouling chemical can affect corals and may impact their metabolism. The finding that Diuron significantly impacts coral tissue fatty acids and metabolism is crucial evidence for classifying marine water quality in sensitive habitats (Class 1) like coral reefs, which are widespread in Malaysian waters. This finding serves as a basis for incorporating Diuron anti-fouling as a parameter in the Malaysian Marine Water Quality Standard (MMWQS). These key policy reforms to protect coral reef ecosystems have multiple benefits for marine ecosystems and humans.